Implementing Virtual Reality in Science Education at South Korean High Schools - Han Jiwon; Seo Jiwon; Nguyen Thi Mai (Journal Emerging Technologies in Education, 2025)
Background. The integration of Virtual Reality (VR) into educational settings has gained global momentum, offering immersive and interactive learning experiences that traditional methods often lack. In South Korea, where academic rigor and technological innovation coexist, there is a growing interest in leveraging VR to enhance science education at the secondary level. Purpose. This study investigates the implementation of VR in science classrooms across selected South Korean high schools, focusing on its pedagogical effectiveness, accessibility, and acceptance among teachers and students. Method. A mixed-methods approach was used, combining quantitative survey data from 312 students and 45 science teachers with qualitative insights from focus group interviews and classroom observations. Results. The findings reveal that VR-based instruction significantly increased student engagement, conceptual understanding, and motivation in learning complex scientific phenomena. However, challenges were noted in terms of teacher training, infrastructure limitations, and curriculum alignment. Conclusion. The study concludes that while VR holds strong potential to transform science education in South Korean high schools, successful implementation requires systemic support, including professional development and policy integration. These insights contribute to the ongoing discourse on future-ready STEM education and provide practical guidance for scalable VR adoption.